E-Cigarette as Distruptive Innovation: Forecasting of conventional cigarette substitution in Indonesia - Erman Aminullah (STI Policy and Management Journal, 2019)
This paper intends to forecast conventional cigarette substitution by e-cigarette in the context of disruptive innovation.  E-cigarette as disruptive innovation  has been driven by   technology innovation to create e-cigarette products for global market. The advancement of e-cigarette technology innovation would continue to create smart and less harmfull e-cigarette  as  alternative tobacco products in future.The results of forecasting show that the replacement of conventional cigarette would be in line with the increase of e-cigarette consumption. The future increase of e-cigarette consumption would be influenced by three factors: (i)  technology advancement, (ii) excise tax incentives, (iii) and tobacco regulation. The diffusion of e-cigarette products in domestic market have raised the level of public acceptance,   despite  still reaped some rejections, especially from the health community in Indonesia.  The  scientific contribution of paper is a system dynamics model on conventional cigarette substitution by e-cigarette’s disruptive innovation. The model is systemic interaction among cigarette consumption, regulators, and public responses both health  community and consumers of e-cigarette in Indonesia. Keywords:  disruptive innovation, product substitution, electric-cigarette, system perspective, forecasting.